OPTIMIZATION OF OIL TANK DESIGN TO MINIMIZE LIQUID SLOSHING IN PORTABLE OIL SPILL SKIMMER - Ramanathan, R.; Maslan, M.N.; Abdullah, L.; Md Fauadi, M.H.F.; Mat Ali, M.; Nur Chairat, A.S. (Journal of Advanced Manufacturing Technology (JAMT), 2023)
When developing an autonomous portable oil spill skimmer, an oil tank is one of the most critical designs to be developed. The problem occurs when large amplitude or resonant frequency excitation which causes violent sloshing that can damage the oil tank structurally or even cause the portable oil spill skimmer to overturn. Therefore, this research aims to analyze liquid sloshing impact in the oil tank, both with and without the baffle. The functionality of the baffle is analyzed to prove that it is crucial to implement a baffle when designing any type of oil tank. Computational Fluid Dynamics (CFD) simulation was used to analyze the liquid sloshing effect in the oil tank as a method in this research. Furthermore, the material selection of the skimmer roller was discussed in this research. Moreover, concept screening and scoring are used to select the best material for the skimmer roller. The result shows that implementing the baffle improves the amplitudes or resonant frequencies of the oil sloshing effect. Additionally, there was a reduction of 96.92% of torque comparing the simulation of with and without baffle. Polypropylene was selected as the best material for the skimmer roller. Essentially, incorporating a baffle in the oil tank minimizes the liquid sloshing effect, thus reducing the pitching and heaving effect on the oil tank.